Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Overexpression of maize asparagine synthetase increases free asparagine and kernel protein in Zea mays - James H. Crowley; Arick Tuhro; Todd Brown; Anabayan Kessavalou; Bradon J. Fabbri; Stephen M. G. Duff (Journal of Plant Biochemistry and Biotechnology, 2025)

Economic impacts of a disease outbreak in Canada’s pork industry: Case of a price-taking, open country - Scott Biden; Alan P. Ker; Bruno Larue; Stephen Duff (Food Policy, 2024)

Expression of a truncated maize SPS increases source capacity in maize - Stephen M. G. Duff; Keith Kretzmer (Journal of Plant Biochemistry and Biotechnology, 2023)
In an attempt to increase source capacity, transgenic corn was generated by expressing a truncated maize sucrose phosphate synthase (ZmSPSΔ482) under two leaf mesophyll cellspecific promoters (CAB and PPDK). The endogenous and truncated SPS proteins from transgenic leaf extracts were distinguishable by protein immunoblot analysis. The expression of transgenic SPS protein across events varied from very low to very high and included several cosuppressed events. SPS activity showed a diurnal pattern in both transgenic and wild-type maize leaves. In greenhouse experiments, transgenic maize had higher leaf sucrose and lower leaf starch, suggesting a shift in carbon partitioning from starch to sucrose. Conversely, cosuppressed events had lower leaf sucrose and higher leaf starch. A field test was performed to compare sucrose and starch in positive and negative isolines of hybrid maize CAB and PPDK ZmSPSΔ482 events. In the field, many positive isolines had higher levels of both leaf sucrose and starch than the negative isolines. This suggests that in the field, with higher light intensity the shift in carbon partitioning from starch to sucrose, observed under greenhouse conditions did not occur. This in turn suggests that the environment affects the phenotype of the transgenics and that in the field, there was an overall increase in carbon assimilation. Six events from each construct were tested in a pilot multi-density yield trial but overall, no effect on yield was observed. Therefore, although the transgenic plants had more source capacity, this did not translate into higher seed yield.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Changes in soil moisture drive soil methane uptake along a fire regeneration chronosequence in a eucalypt forest landscape - Benedikt Fest; Tim Wardlaw; Stephen J. Livesley; Thomas J. Duff; Stefan K. Arndt (Global Change Biology, 2015)
Disturbance associated with severe wildfires (WF) and WF simulating harvest operations can potentially alter soil methane ( CH 4 ) oxidation in well‐aerated forest soils due to the effect on soil properties linked to diffusivity, methanotrophic activity or changes in methanotrophic bacterial community structure. However, changes in soil CH 4 flux related to such disturbances are still rarely studied even though WF frequency is predicted to increase as a consequence of global climate change. We measured in‐situ soil–atmosphere CH 4 exchange along a wet sclerophyll eucalypt forest regeneration chronosequence in Tasmania, Australia, where the time since the last severe fire or harvesting disturbance ranged from 9 to >200 years. On all sampling occasions, mean CH 4 uptake increased from most recently disturbed sites (9 year) to sites at stand ‘maturity’ (44 and 76 years). In stands >76 years since disturbance, we observed a decrease in soil CH 4 uptake. A similar age dependency of potential CH 4 oxidation for three soil layers (0.0–0.05, 0.05–0.10, 0.10–0.15 m) could be observed on incubated soils under controlled laboratory conditions. The differences in soil CH 4 uptake between forest stands of different age were predominantly driven by differences in soil moisture status, which affected the diffusion of atmospheric CH 4 into the soil. The observed soil moisture pattern was likely driven by changes in interception or evapotranspiration with forest age, which have been well described for similar eucalypt forest systems in south‐eastern Australia. Our results imply that there is a large amount of variability in CH 4 uptake at a landscape scale that can be attributed to stand age and soil moisture differences. An increase in severe WF frequency in response to climate change could potentially increase overall forest soil CH 4 sinks.

Tradeoffs in Overstory and Understory Aboveground Net Primary Productivity in Southwestern Ponderosa Pine Stands - Kyla E. Sabo; Stephen C. Hart; Carolyn Hull Sieg; John Duff Bailey (Forest Science, 2008)
Previous studies in ponderosa pine forests have quantified the relationship between overstory stand characteristics and understory production using tree measurements such as basal area. We built on these past studies by evaluating the tradeoff between overstory and understory aboveground net primary productivity (ANPP) in southwestern ponderosa pine forests at the landscape level and over a gradient of stand structural types and burn histories. We measured overstory and understory attributes in 2004 and 2005 in four stand structural types (unmanaged, thinned, thinned and burned, and low basal area thinned and burned) relative to a stand-replacing wildfire site. Thinning alone and with prescribed burning reduced stand-level wood and total tree production relative to unmanaged stands. Understory (herbaceous) ANPP was highest in wildfire stands and low basal area thinned and burned plots but did not differ among the other stand structural types, apparently because of high residual basal area and relatively uniform tree spacing. Contemporary ponderosa pine forests are low productivity ecosystems that exhibit a threshold response between reductions in tree density and increases in understory production at 5.9 m2 ha. We calculated the slope of the relationship between tree and herbaceous ANPP to be −0.14, which was lower than the values we estimated from other, more productive savanna ecosystems. Our results suggest that to maintain more fire-resistant and hence sustainable southwestern ponderosa pine ecosystems, tree densities need to be substantially reduced from contemporary levels. Large, landscape-level reductions in tree density will decrease total ecosystem production of this forest type, but this reduction will probably be small relative to ecosystem production losses after widespread, stand-replacing wildfires.

A genetic comparison of two species of clam shrimp in the genus Eulimnadia: An electrophoretic approach - Stephen C. Weeks; R. Joel Duff (Hydrobiologia, 2002)